PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS VII SMPN 19 PADANG - Wulan, Embun Sari (Jurnal Edukasi dan Penelitian Matematika, 2023)
– The ability to solve mathematical problems is one of the skills expected to be owned and developed in mathematics learning. However, in reality the problem solving ability in mathematical of students from class VII SMPN 19 Padang is still not optimal. To respond these problems, solution are made to use the Problem Based Learning model. The research purpose was to look whether the problem solving skills in mathematical of students in class VII SMPN 19 Padang who studied using the model of Problem Based Learning were better than those who studied using conventional learning models. The research type used was quasi-experimental through The Nonequivalent Pretest-Posttest Control Group Design. The population for research was class VII students of SMPN 19 Padang. The instrument for research used was the pretest (pretest) and posttest (posttest) of problem solving ability in mathematical. Based on the final test results of hypothesis test (posttest) mathematical problem solving ability with α = 0.05 obtained P-Value <α, which means ?0 is rejected. We got conclussion that the skills of problem solving in mathematical of students who studied using the model of Problem Based Learning were better than those who studied using conventional learning models.Keywords– Mathematical Problem Solving Ability, Problem Based Learning Models, Conventional Learning Models.